2017
DOI: 10.1002/cbin.10291
|View full text |Cite
|
Sign up to set email alerts
|

Retracted: Sirt3 activation attenuated oxidized low‐density lipoprotein‐induced human umbilical vein endothelial cells’ apoptosis by sustaining autophagy by Luo, X, Yang, Z, Zheng, S, Cao, Y and Wu, Y

Abstract: The above article, published online on 05 May 2014 in Wiley Online Library (http://onlinelibrary.wiley.com/doi/10.1002/cbin.10291/full), has been retracted by agreement between the authors, the journal Editor, Sergio Schenkman, and John Wiley & Sons Ltd. The retraction has been agreed because the authors discovered that the results of section 3 in this paper were irreproducible. In addition, Zhiqiang Yang, a co-author, states conflict of interest in this paper. The authors and publisher apologize for any incon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Our results that knockdown of Sirt3 expression partially prevented the autophagy and protection induced by resveratrol, further supported the involvement of Sirt3 in autophagy regulation in neuronal cells, and indicated that resveratrol-induced protective effects were mediated by Sirt3 signaling. However, the role of Sirt3 in autophagy regulation has not been fully determined, especially some results was shown to be irreproducible ( 2017 ), and thus, some more experiments in gene knockout animals need to be performed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Our results that knockdown of Sirt3 expression partially prevented the autophagy and protection induced by resveratrol, further supported the involvement of Sirt3 in autophagy regulation in neuronal cells, and indicated that resveratrol-induced protective effects were mediated by Sirt3 signaling. However, the role of Sirt3 in autophagy regulation has not been fully determined, especially some results was shown to be irreproducible ( 2017 ), and thus, some more experiments in gene knockout animals need to be performed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that downregulation of SIRT3 promotes the apoptosis of alveolar epithelial cells ( 26 ) and EC9706 cells ( 27 ). Studies have also shown that SIRT3 protects tumor cells against apoptosis under unfavorable environments, such as hypoxia ( 28 ), oxidized low-density lipoprotein ( 29 ) and high glucose levels ( 30 ). However, the expression of SIRT3 and its effect on apoptosis and bronchial inflammation in asthma remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…a key enzyme in the metabolic regulation and ROS homeo-435 stasis during vascular disease[95][96][97] (Fig. 2).…”
mentioning
confidence: 99%